Nuclear physics technique for adjacent regions - Dikiy, N.P. (Вопросы атомной науки и техники, 2003)
Development of nuclear physics technique at electrostatic accelerates of NSC KIPT are given. These methods allow analysing the elements from hydrogen isotopes to transuranium elements. Using of resonance nuclear reactions are especially effective for interstitial impurity, which essentially influence on properties of constructional materials. It is described using of combined methods. The nuclear-physical data for biology and medicine are given.